Blockchain-Enabled Digital Financial Systems in Islamic Banking: Evidence from a Systematic Literature Review - Rihfenti Ernayani (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This study provides a comprehensive review of blockchain-based digital financial systems in Islamic banking, synthesizing recent developments, challenges, and prospects for integrating blockchain within Shariah-compliant financial institutions. Using a qualitative systematic literature review approach, data were collected from peer-reviewed theoretical and empirical studies indexed in Google Scholar and Mendeley Data. The review systematically examines research methodologies, technological applications, and their implications for Islamic finance. The findings indicate that blockchain adoption significantly enhances security, transparency, and operational efficiency in Islamic banking processes. However, critical challenges persist, particularly regarding Shariah compliance, governance mechanisms, and the alignment of blockchain applications with Islamic ethical principles. The study highlights key determinants influencing blockchain adoption, including governance structures, regulatory readiness, and Shariah oversight. To address existing gaps, this research integrates Shariah principles into the analytical framework, ensuring that ethical values remain central to digital financial innovation. The study contributes to the literature by mapping blockchain research to the core functions of Islamic banks and by proposing a Sharia-compliant blockchain system model, along with a future research roadmap. In practice, the findings provide strategic guidance for Islamic banks on implementing smart contracts, strengthening Shariah audits, reducing operational costs, and fostering digital product innovation.